2013
DOI: 10.3109/0886022x.2013.832318
|View full text |Cite
|
Sign up to set email alerts
|

Hot bath for the treatment of chronic renal failure

Abstract: Background: Dialysis and its complications were debated recently. There was lack of an adjuvant renal replacement method to reduce the complications of patients with chronic renal failure and dialysis itself. Materials and methods: In this article, we reviewed the role of thermal sweating in treating of the patients with chronic renal failure, and the role of traditional Chinese medicine in the therapy of chronic kidney diseases. Results: Thermal sweating can reduce interdialytic weight gain and improve the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…However, this explanation is mainly speculative and whether there are any beneficial effects of sauna exposure on renal function warrants further investigation. In a comprehensive review of the role of hot baths for the treatment of chronic renal failure, the authors concluded that hot baths had the potential to clear uremic toxins by skin eccrine sweating and decrease the frequency of adverse events in patients with chronic renal failure 37 . In a rodent model of chronic kidney disease, mild systemic thermal therapy was effective at ameliorating renal dysfunction 38 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this explanation is mainly speculative and whether there are any beneficial effects of sauna exposure on renal function warrants further investigation. In a comprehensive review of the role of hot baths for the treatment of chronic renal failure, the authors concluded that hot baths had the potential to clear uremic toxins by skin eccrine sweating and decrease the frequency of adverse events in patients with chronic renal failure 37 . In a rodent model of chronic kidney disease, mild systemic thermal therapy was effective at ameliorating renal dysfunction 38 .…”
Section: Discussionmentioning
confidence: 99%
“…In a comprehensive review of the role of hot baths for the treatment of chronic renal failure, the authors concluded that hot baths had the potential to clear uremic toxins by skin eccrine sweating and decrease the frequency of adverse events in patients with chronic renal failure. 37 In a rodent model of chronic kidney disease, mild systemic thermal therapy was effective at ameliorating renal dysfunction. 38 Both observational and interventional evidence suggests that sauna reduces blood pressure and the risk of hypertension, which is a major risk factor for chronic kidney disease.…”
Section: Cross-sectional Association (Baseline)mentioning
confidence: 99%
“…It involves a three step process where the sample is digested using concentrated sulphuric acid and with various catalysts, then the obtained ammonium salt is converted to ammonia followed by a distillation procedure and finally the dissolved ammonia is determined (Purificación et al 2013). In sweat, urea, uric acid, creatinine and ammonia contribute to the presence of nitrogen with respective concentrations of 22.2±8.0 mmol l −1 , 0.025±0.0007 mmol l −1 , 0.031±0.017 mmol l −1 and 6±3 mmol l −1 (Consolazio et al 1963, Ament et al 1997, Houltham and Rowlands 2014, Ye et al 2014. Any change in urea concentration will directly influence nitrogen concentration.…”
Section: Discussionmentioning
confidence: 99%
“…As an ancient therapeutic method, Chinese herbal bath therapy (CHBT) has been used for thousands of years in China [14, 15]. In the early published Chinese medical works, such as “Prescriptions for fifty-two diseases” (202 B.C.-9 A.D.) and “Treatise on Cold Pathogenic and Miscellaneous Diseases” (200 A.D.- 210 A.D.), herbal bath therapy was frequently used [15].…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, herbal bath therapy is still very popular in Asian countries today and is widely used to treat skin diseases, osteoarthritis diseases and some internal diseases, of which pruritus is especially responsive [16]. While traditional Chinese medicine doctors use herbal baths to relieve itching in patients with uraemia, the mechanism of the effect is not particularly clear [14, 17].…”
Section: Introductionmentioning
confidence: 99%